1994
DOI: 10.1200/jco.1994.12.12.2543
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of autologous bone marrow transplantation with sequential chemotherapy for intermediate-grade and high-grade non-Hodgkin's lymphoma in first complete remission: a study of 464 patients. Groupe d'Etude des Lymphomes de l'Adulte.

Abstract: For such a subset of patients, consolidation with the CBV regimen followed by autologous bone marrow transplantation is not superior to sequential chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0
3

Year Published

1996
1996
2012
2012

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 181 publications
(50 citation statements)
references
References 20 publications
2
45
0
3
Order By: Relevance
“…For these patients, more intensive regimens should be tested 18 or high-dose therapy with autologous stemcell transplantation. 15,19 In conclusions, PCLL behave like other localized B or T large-cell extranodal lymphomas with the same prognostic factors (LDH level, ECOG score, age), except for CD30 + PCLL which have a better prognosis than nodal CD30 + malignant lymphomas. 20 Treatment should be tailored according to immunohistology and extent of the cutaneous disease.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…For these patients, more intensive regimens should be tested 18 or high-dose therapy with autologous stemcell transplantation. 15,19 In conclusions, PCLL behave like other localized B or T large-cell extranodal lymphomas with the same prognostic factors (LDH level, ECOG score, age), except for CD30 + PCLL which have a better prognosis than nodal CD30 + malignant lymphomas. 20 Treatment should be tailored according to immunohistology and extent of the cutaneous disease.…”
Section: Discussionmentioning
confidence: 85%
“…One patient recieved late intensification with highdose therapy (CBV) and autologous bone marrow transplantation. 15 No adjustment was made for hematological toxicity, but chemotherapy was delayed until the neutrophil count was above 1000 × 10 9 /l and platelet count above 100 000 × 10 9 /l. No radiation therapy was recommended in the protocol, but 2/49 patients received radiotherapy to localized cutaneous lesions.…”
Section: Treatmentmentioning
confidence: 99%
“…A clinical improvement was observed after the first course of NCVBP chemotherapy (mitoxantrone 12 mg/m 2 day 1, cyclophosphamide 1200 mg/m 2 day 1, vinblastine 2 mg/m 2 days 1 and 5, bleomycine 10 mg days 1 and 5, prednisone 60 mg/m 2 from day 1 to day 5, intrathecal methotrexate 12 mg day 1). 20 Despite CNS prophylaxis, a meningeal relapse occurred after the third course. The patient received salvage chemotherapy with IVAM regimen (ifosfamide 1500 mg/m 2 daily for 5 days + mesna, etoposide 150 mg/m 2 daily for 3 days, cytarabine 100 mg/m 2 daily for 3 days, methotrexate 3 g/m 2 at day 5 with leucovorin rescue) 21 followed by an autologous peripheral blood stem cell transplantation.…”
Section: Figurementioning
confidence: 99%
“…53 However, this trial was instituted before the publication of the IPI, and treatment-related differences became apparent when study patients were retrospectively grouped into risk groups according to the age-adjusted IPI. In the retrospective analysis, 451 patients were determined to be high-intermediateor high-risk IPI patients (two risk factors, n ¼ 318; three risk factors, n ¼ 133), and 277 (61%) achieved CR and were eligible for the randomization to HDT or chemotherapy.…”
Section: Treatment With Hdtmentioning
confidence: 99%
“…In the majority of these trials, poor-risk disease was identified by criteria other than the IPI or age-adjusted IPI. Various paradigms for upfront HDT were investigated, namely, following a CR after a full course of induction therapy; 53,55 following a full course of induction therapy, regardless of response; 57 following a CR or PR 58 or 'minor' response 60 after abbreviated standard-dose chemotherapy or abbreviated dose-intense chemotherapy; 56,59,61 and following a 'slow' response to induction chemotherapy 54 (Table 5 and 6). …”
Section: Treatment With Hdtmentioning
confidence: 99%